Repairing Breaches with Rules: Maintaining Institutions in the Face of Everyday Disruptions - Heaphy, Emily D. (Organization Science, 2013)
This study reveals the institutional work required to maintain taken-for-granted beliefs about roles in the face of everyday breaches of role expectations. Through a comparative qualitative study of hospital-employed patient advocates in teaching and Veterans Health Administration hospitals, I demonstrate that patient advocates repair breaches in the taken-for-granted beliefs about the patient, family, and staff roles in hospitals. My research shows that patient advocates skillfully used rules—or formal policies and procedures—to restore, clarify, or initiate organizational changes in rules, all to maintain institutionalized role expectations. This analysis expands our understanding of the work of maintaining institutions by specifying how constellations of roles are maintained in the face of breaches of role expectations and across different institutional contexts. It highlights the roles of pressure specialists and furthers theorizing on individual agency by specifying how rules can be source of individual agency.